A formação leitora no livro didático de História - Marco Antonio da Silva (2009)
This research investigated the concepts and strategies for the development of reading and literacy in history in the teaching collection Araribá Project - History. The collection presents a proposal to develop the competence of reading which indicates the reader was one of the reasons that made the work more adopted by teachers in the Brazilian National Program of Textbooks (PNLD) in its 2009 edition. The theoretical and methodological reasons were the intercession of literature from different fields of knowledge and, among these, we highlight the production of Roger Chartier (2003) about the history of reading and the book, Mary Kato (1995), Angela Kleiman ( 1993, 1996) and of Isabel Solé (1998) in the field of psicolinguistics; of Magda Soares (2002, 2005) in the Education and Lopes de Macedo (2002) and Dias (2003) on the concept of competence, work on teaching of history Bittencourt (1993, 2004) and Munakata (1997), for reading and writing in History of Ainsenberg (2005) and Mattozzi (2004); Rüsen on literacy in History (2006, 2007), Peter Lee (2001, 2003 and 2006) and Isabel Barca (2006); propositions on the official reading of History in the National Curriculum Parameters and Guidelines for supervision of teachers of the Secretary of Education of São Paulo (2006). This study describes the current stage of production in relation to academic concepts of reading, reading in history, literacy and literacy in history and discusses how these concepts are present in the textbook mentioned above. Moreover, it demonstrates how the teaching of reading has been studied in the literature and Incorporated into the textbooks as a responsibility of teachers in various disciplines that comprise the school curriculum In the final series of elementary school. It is discussed how successful the reader is associated with the proficient use of a variety of reading strategies that can be taught to students who have literacy deficiencies in textual interpretation in history and in diverse disciplines of the school curriculum. Finally, we face the propositions for the teaching of readingproposed in academic literature with those adopted by textbook earched.